Sculpture of yogini affixed on the compound of Bhairon Temple - Temples of India Project Team (Jio Institute, 2024)
Independent sculpture of yogini affixed on the Bhairon compound near the entry of the main shrine in the basement. This is one of the many images of yoginis found at the site hinting at a lost yogini temple compound. Contextualizing this image with several other relevant images suggests a maturity of Shakti and tantric traditions at the site. Her arms are lost, and she sits in the lalitasana posture.